2011
DOI: 10.3357/asem.3047.2011
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Phenotype and Cytokine Production Profiles Are Dysregulated by Short-Duration Spaceflight

Abstract: These data indicate that changes in monocyte constitutive phenotype and inflammatory cytokine production occur following short-duration spaceflight, which may impact overall crewmember immunocompetence. Also, monocyte/macrophage function may be highly sensitive to mission specific parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
72
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 26 publications
(5 reference statements)
8
72
0
2
Order By: Relevance
“…Additionally, because of their ability to colonize the human body and produce toxins, volatile organic compounds, and proteases, the common molds ( Alternaria , Cladosporium , Epicoccum ) could damage airways of immunocompromised occupants, which make them more dangerous than any other allergenic source [8285]. In this study, accumulation of Alternaria and Epicoccum genera over time was observed, which, in combination with reported decreased immunity in occupants of confined spaces, e.g., astronauts [50, 86] could lead to developing allergy and asthma symptoms.…”
Section: Discussionmentioning
confidence: 73%
“…Additionally, because of their ability to colonize the human body and produce toxins, volatile organic compounds, and proteases, the common molds ( Alternaria , Cladosporium , Epicoccum ) could damage airways of immunocompromised occupants, which make them more dangerous than any other allergenic source [8285]. In this study, accumulation of Alternaria and Epicoccum genera over time was observed, which, in combination with reported decreased immunity in occupants of confined spaces, e.g., astronauts [50, 86] could lead to developing allergy and asthma symptoms.…”
Section: Discussionmentioning
confidence: 73%
“…Many years later, another immune system disturbance was discovered exhibiting latent virus reactivation such as varicella zoster 7, 8 . Since the first evidences of a compromised immune system in space, sensitivity of cells of the human immune system to reduced gravity has been confirmed by numerous studies in real and simulated microgravity 9–15 . However, the mechanisms underlying gravity-regulated cellular responses are still unknown.…”
Section: Introductionmentioning
confidence: 94%
“…Parabolic flight induces an increase in PMN number and the capability of PMNs to produce hydrogen peroxide (H 2 O 2 ) in response to soluble stimuli (Kaufmann et al 2009). These works seemingly indicate that the action of microgravity has enhanced the immune response of PMNs, which is inconsistent with the reduced capability of lymphocytes (Cogoli and Tschopp 1985;Konstantinova et al 1993;Meshkov and Rykova 1995;Mills et al 2002;Mills et al 2008Mills et al , 2013, monocytes (Kaur et al 2005(Kaur et al , 2008Crucian et al 2011), NK cells (Rykova et al 1992;Konstantinova et al 1993Konstantinova et al , 1995Mehta et al 2001), and macrophages (Armstrong et al 1995;Hsieh et al 2005;Ortega et al 2012;Adrian et al 2013;Wang et al 2014Wang et al , 2015Brungs et al 2015;Paulsen et al 2015) under microgravity. The underlying mechanisms for such the difference remain unclear.…”
Section: Introductionmentioning
confidence: 97%